Design and development of intelligent adaptive tunnel lighting system - Musa, M.S. (Institute of Electrical and Electronics Engineers Inc., 2015)
The Intelligent adaptive tunnel lighting system is a design approach in which the tunnel interior lighting system adapts to the real time roadway environment conditions. The level of tunnel lighting can be reduced or dimmed when the intensity of tunnel exterior daylight is decreased. Moreover, it can also be reduced when traffic on access road to the tunnel is absent. Dimming the luminaries to meet the minimum requirements would save on power consumption as well as maintenance costs. An adaptive tunnel lighting system is developed with the purpose of providing sufficient tunnel interior luminance so that motorist can access and exit the tunnel conveniently. Three levels were developed with integration of motion and light sensors. The results indicate that average of 22.1 of power consumption can be reduced by using this system. Furthermore, LED is highly recommended to be use in the system due to its luminous efficiency and long lifecycle. Â© 2015 IEEE.